(untitled) (Journal of Medical & Health Sciences Review, 2025)
Basic Life Support (BLS) refers to a set of emergency procedures, including cardiopulmonary resuscitation (CPR), use of an automated external defibrillator (AED), and management of airway obstruction, aimed at sustaining life in cases of cardiac or respiratory arrest. This study aims to assess the current level of knowledge and practices related to BLS among health care professionals in a tertiary care hospital in Lahore. This descriptive cross-sectional study assessed the knowledge and practices of 100 health care professionals regarding Basic Life Support (BLS) at a tertiary care hospital in Lahore. Participants included doctors, nurses, and paramedical staff with at least six months of clinical experience, selected through stratified random sampling. Data were collected using a validated, structured questionnaire based on AHA guidelines. The questionnaire covered demographics, knowledge, and practice through multiple-choice and scenario-based questions. Data were analyzed using SPSS version 25, with ethical approval obtained from the Institutional Review Board of Jinnah Hospital Lahore. The results showed that most participants were aged 21–35 years (40%) and male (55%). Professionally, 42% were nurses, 38% paramedical staff, and 20% doctors, with the highest representation from the general ward (42%). Nearly half (48%) had less than one year of experience. Regarding BLS knowledge, 53% had poor knowledge, 30% moderate, and only 17% had good knowledge. In terms of practice, 73% demonstrated incompetent practices, highlighting a significant gap between knowledge and practical application of BLS among health care professionals.